INFLUENCE OF SLOT CHANNEL PARAMETERS ON AERODYNAMICS CHARACTERISTICS OF TANDEM CASCADE - Терещенко, Ю.М.; Дорошенко, К.В.; Аболхассан заде, Дж. (Science-based technologies, 2015)
Using of tandem cascade in stator of multistage axial-flow compressor is effective method for improving of compressor performance. Tandem vanes supply power improving of stage on operating regime and increasing of stalling compressor performance at non operating regimes at big positive angles of attack. The aim of work was to research influence of slot channel parameters of tandem airfoil cascades on value of cascade quality parameter at positive and negative angles of attack. Analysis of the calculation results showed that at positive angles of attack tandem cascades are flowed without flow separation. But vortex flow is conformed on vane surface of geometrical equivalent simple cascade. Cascade quality parameter of tandem cascade is higher than simple cascade at positive and negative angles of attack. Aerodynamics characteristics of tandem cascade essentially depend on vane chord ratio of first and second row.